Rekonstruksi Pembuktian Mens Rea bagi Kurir Narkoba Berdasarkan Doktrin Willful Blindness - Linda Ikawati; Rengga Kusuma Putra; Satriya Nugraha; Retno Eko Mardani; Aziz Widhi Nugroho (SPEKTRUM HUKUM, 2026)
Narcotics law enforcement in Indonesia faces a paradoxical crisis where repressive criminal policies coexist with simplified evidence standards that often overlook the fundamental element of criminal liability: mens rea. Legal practice frequently adopts a de facto strict liability approach, where physical possession of narcotics automatically equates to guilty intent. This creates a substantive injustice, particularly for "instant couriers" who may be victims of deception (innocent agents). This research aims to reconstruct the evidentiary model of mens rea by adopting the "willful blindness" doctrine as an analytical bridge within the framework of the National Penal Code (dolus eventualis). Using a normative legal method with a conceptual and case-based approach, this study proposes a systematic reconstruction through objective indicators known as "Red Flags," such as unreasonable compensation and suspicious delivery patterns. The findings suggest that when a courier deliberately avoids confirming high-probability illegality, they should be held liable under a reconstructed mens rea standard. The implication of this study is the necessity of a standardized judicial guideline to distinguish between honest mistakes and epistemic strategies, ensuring a more proportional and human rights-oriented justice system.